Case Study of Income Inequality, Governance, and Economic Growth in EMCCA Countries - Djaowe , Joseph (An Overview on Business, Management and Economics Research Vol. 2, 2023)
The aim of this study is to examine the influence of governance and income inequality on economic growth in the six member nations of the Economic and Monetary Community of Central Africa (EMCCA) that are in the process of emerging. The poor performance of the sub-regional economy during the last few years can be explained in part by poor governance and unfair resource reallocation. Despite these nations' abundant natural riches, it has been proved that poverty is spreading swiftly. This has a greater impact on rural communities than on metropolitan places. The majority of theoretical and empirical surveys conducted provide contentious outcomes about the relationship between inequality and growth. The dynamic panel assessment results show that: (1) Income inequality has a negative impact on economic growth in EMCCA countries, (2) the composite index of governance has a positive impact on the growth rate of the effective Gross Domestic Product (GDP) individually, and (3) the interaction between income disparity and governance has a negative impact on economic growth.